Prognosis in metastatic lung cancer: vitamin D deficiency and depression—a cross-sectional analysis. Issue 3 (27th August 2020) - McFarland, Daniel C; Fernbach, Madalyn; Breitbart, William S; Nelson, Christian
Abstract : Background: Depression and vitamin D deficiency are common in patients with lung cancer and have prognostic implications in cancer settings. However, their relationship and concomitant survival implications have not been evaluated in patients with metastatic lung cancer specifically. We hypothesised that vitamin D deficiency would be associated with depression and inferior cancer-related survival in patients receiving therapies for stage IV lung cancer. Methods: This was a cross-sectional analysis of vitamin D, depression and lung cancer characteristics. Vitamin D levels were stratified by level (no deficiency ≥30 units, mild deficiency 20 to 29 units and moderate-to-severe <20 units). Depression was measured by the Hospital Anxiety and Depression Scale-Depression (HADS-D). Survival estimations were made using Cox proportional hazard model and Kaplan-Meier analyses. Results: Vitamin D deficiency was evident in almost half of the sample (n=98) and was associated with significant depression (HADS-D ≥8) (χ 2 =4.35, p<0.001) even when controlling for age, sex and inflammation (β=-0.21, p=0.03). Vitamin D deficiency and depression were associated with worse survival and showed evidence of an interaction effect (HR 1.5, p=0.04). Conclusion: Vitamin D deficiency is associated with depression in patients with metastatic lung cancer. Depression modulates the survival implications of vitamin D deficiency in this population. The role of vitamin D deficiency in cancer-related depression warrants further investigation since both are amenable to treatment. Psychological and nutritional prognostic considerations may help inform treatment paradigms that enhance quality of life and survival.